" Obbedite alle autorità costituite " Sacralità del potere e possibilità della disobbedienza nella riflessione politica medievale - Simonetta, Stefano 1968- (2023)
Chapter 13 of The Epistle to the Romans lays the foundations on which the whole conception of power in medieval political thought is based. The aim of this paper is to reconstruct the long-term process through which the Latin West gradually came to admit and theorise the possibility of disobeying temporal authorities, albeit within a theoretical framework of power (namely the Pauline-Augustinian one), which would seem to leave no room for dissent, conferring on every potestas a divine origin and providential nature. The author traces the main stages of this process : from the idea that in order to obtain unconditional obedience from one's subjects, one must show oneself a " rex christianissimus " (protecting both the persons and property of Christ's ministers), to the difficult legitimisation of tyrannicide in John of Salisbury ; from the pages of Thomas Aquinas on the deposition of a ruler who does not care about the communis utilitas, to the explicit recognition of the power to dismiss secular lords by some political theorists of the 14th and 15th centuries.
Le chapitre 13 de l'Épître aux Romains pose les bases sur lesquelles repose toute la conception du pouvoir dans la pensée politique médiévale. L'objectif de cet article est de reconstruire le processus de longue durée par lequel l'Occident latin a progressivement admis et théorisé la possibilité de désobéir aux autorités temporelles, bien que dans le cadre d'une théorie du pouvoir (à savoir la théorie paulino-augustinienne du pouvoir), qui semble ne laisser aucune place à la dissidence, conférant à chaque potestas une origine divine et une nature providentielle. L'auteur retrace les principales étapes de ce processus : de l’idée que pour obtenir l’obéissance inconditionnelle de ses sujets, il faut se montrer " rex christianissimus " (protéger les personnes et les biens des ministres du Christ), à la difficile légitimation du tyrannicide chez Jean de Salisbury ; des pages de Thomas d'Aquin sur la déposition d'un souverain qui ne se soucie pas de la communis utilitas, à la reconnaissance explicite du pouvoir de destitution des seigneurs séculiers par certains théoriciens politiques des xive et xve siècles.
Keywords: Droit de résistance; Impôts; Mediaeval political thought; Pensée politique médiévale; Right of resistance; Souverains temporels; Taxes; Temporal rulers; Tyrannicide